2018
DOI: 10.1093/jeea/jvx057
|View full text |Cite
|
Sign up to set email alerts
|

Gender Bias in Teaching Evaluations

Abstract: *This paper provides new evidence on gender bias in teaching evaluations. We exploit a quasi-experimental dataset of 19,952 student evaluations of university faculty in a context where students are randomly allocated to female or male instructors. Despite the fact that neither students' grades nor self-study hours are affected by the instructor's gender, we find that women receive systematically lower teaching evaluations than their male colleagues. This bias is driven by male students' evaluations, is larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
197
1
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 307 publications
(253 citation statements)
references
References 51 publications
(39 reference statements)
20
197
1
6
Order By: Relevance
“…Interacting gender with experience did not have significant effects, but there are indications that women are able to make up for some of the gender bias through experience, at least initially. This rhymes with the results of Mengel et al (2017) who found that the gender bias in SET is particularly pronounced for junior women, but less so for senior female faculty.…”
Section: Discussion and Recommendationssupporting
confidence: 85%
See 4 more Smart Citations
“…Interacting gender with experience did not have significant effects, but there are indications that women are able to make up for some of the gender bias through experience, at least initially. This rhymes with the results of Mengel et al (2017) who found that the gender bias in SET is particularly pronounced for junior women, but less so for senior female faculty.…”
Section: Discussion and Recommendationssupporting
confidence: 85%
“…They also value female instructors' teaching performance less than male instructors' as well as finding female instructors less accessible. These results are in line with Boring (2015), where she found that being a female teacher decreased the likelihood of obtaining a higher satisfaction score, Mengel et al (2017) who find that women get systematically lower scores than men, and MacNell et al (2015) who found that students made more demands on perceived female instructors than perceived male instructors. Although the simple model, Model 1, showed women receiving consistently lower SET than men, the size of the effect was much larger in Model 2, when the gender effect was also interacted with the independent variables experience, co-teaching, part-time instructor, and class size.…”
Section: Discussion and Recommendationssupporting
confidence: 76%
See 3 more Smart Citations